Perioperative and Periprocedural Care of Patients With Intrathecal Pump Therapy. Issue 7 (31st October 2018) - Nadherny, Weston; Anderson, Brooke; Abd‐Elsayed, Alaa
Abstract : Introduction: There are an ever‐increasing number of patients who have implanted devices for targeted delivery of drug therapy to the intrathecal space for the management of spasticity or chronic pain. This leads to a growing number of people with implanted pumps presenting for procedures and surgeries, yet there is a paucity of consolidated information available to describe the appropriate precautions and patient management during this period. Methods: This was a systematic review to provide a summary of existing literature on intrathecal drug delivery system (IDDS) management in the perioperative and procedural period, and to highlight additional areas that require further research. Topics addressed include the time surrounding magnetic resonance imaging, defibrillation, radiation therapy, high output ultrasound, lithotripsy, ablation, diathermy, electroconvulsive therapy, and the perioperative period, all of which have their own specific considerations. Results: A total of 42 articles met criteria to be included in this review. Inclusion criteria were English language, and that the article was primarily focused on the perioperative or periprocedural management of IDDSs. Exclusion criteria included commentaries, surveys, published abstracts, or articles that did not discuss the perioperative or periprocedural care of IDDS. Conclusion: Our article outlined perioperative considerations when dealing with a patient with intrathecal pump undergoing surgical or imaging modality.